2023
DOI: 10.3389/fpsyg.2023.1131506
|View full text |Cite
|
Sign up to set email alerts
|

The use of chatbots in university EFL settings: Research trends and pedagogical implications

Abstract: This mini-review aims to identify major research trends, models, and theories and provide specific pedagogical implications for teaching when using chatbots in EFL classes. This study follows the guidelines of the PRISMA methodology and searches for open-access empirical studies in two reputable databases, Web of Science and Scopus. The results of this mini-review confirm the findings of other research studies, which show that the present research on the use of chatbots in university EFL settings focuses on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…As three participants (I01, I03 I06) were international students and non-native English speakers, they found it useful having an AIDA that would work in different languages. Preliminary evidence shows that Gen AI approaches could be useful for language acquisition of non-native English speakers (Klímová & Ibna Seraj, 2023). At the same time, some like IO9, who is a native English speaker but from a particular region in the UK, was worried about whether or not AI would pick up her respective accent.…”
Section: Results From the Interview: Expected Services From Aida Acco...mentioning
confidence: 99%
“…As three participants (I01, I03 I06) were international students and non-native English speakers, they found it useful having an AIDA that would work in different languages. Preliminary evidence shows that Gen AI approaches could be useful for language acquisition of non-native English speakers (Klímová & Ibna Seraj, 2023). At the same time, some like IO9, who is a native English speaker but from a particular region in the UK, was worried about whether or not AI would pick up her respective accent.…”
Section: Results From the Interview: Expected Services From Aida Acco...mentioning
confidence: 99%
“…Within EFL writing courses, the adoption of chatbots has significant pedagogical consequences. Research by Klimova and Seraj (2023) explored key trends, models, and theories, offering specific teaching strategies for employing chatbots in EFL writing classes, including their use in prewriting activities and assessments. They found that students utilising mind mapping techniques generally achieve higher academic success and exhibit more logical thinking and noted the effectiveness of chatbots in evaluating students' writing abilities (Klimova & Seraj, 2023).…”
Section: Pedagogical Implications Of Integrating Ai Chatbots Into Efl...mentioning
confidence: 99%
“…Research by Klimova and Seraj (2023) explored key trends, models, and theories, offering specific teaching strategies for employing chatbots in EFL writing classes, including their use in prewriting activities and assessments. They found that students utilising mind mapping techniques generally achieve higher academic success and exhibit more logical thinking and noted the effectiveness of chatbots in evaluating students' writing abilities (Klimova & Seraj, 2023). Yang's (2022) study further highlighted the role of AI chatbots in EFL writing instruction, stressing the need for an educational environment that nurtures multilingual students' literacy-mediated identities, integrating their previous literacy experiences with a dialogical teaching approach and a research-driven, multiple-draft strategy.…”
Section: Pedagogical Implications Of Integrating Ai Chatbots Into Efl...mentioning
confidence: 99%
“…Additionally, studies like [21] and [22] propose innovative architectures, [23] and [24] integrate chatbots with CALL systems, and [25], [26], and [27] scrutinize linguistic accuracy and pedagogical implications. Further investigations, like [28], [29], and [30], explore cognitive and motivational aspects, while [31], [32], and [33] discuss emerging trends and educational roles.…”
Section: Emotional Aspectmentioning
confidence: 99%